2022
DOI: 10.1186/s40337-022-00550-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes of symptoms of eating disorders (ED) and their related psychological health issues during the COVID-19 pandemic: a systematic review and meta-analysis

Abstract: Background The COVID-19 pandemic and its related social restrictions have profoundly affected people’s mental health. It can be assumed that symptomatic behaviors and mental health of individuals with eating disorders (ED) deteriorated during this time. To get a thorough overview, we conducted a systematic review and meta-analysis with the following aims: First, to provide a comprehensive overview of symptoms of ED during the COVID-19-related confinement; second, to identify psychological mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 69 publications
2
38
0
1
Order By: Relevance
“…Although these disorders are most often diagnosed in young girls and mainly affect Western cultures, they can occur in people of any gender, age, and background [ 11 ]. Recent years have been particularly challenging for people with eating disorders due to the COVID-19 pandemic, as restrictions on social life and difficult access to medical professionals may have negatively affected their mental health [ 16 , 17 ]. It was observed that in 2020, rates of eating disorder symptoms, depression, and anxiety were higher than in previous years [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these disorders are most often diagnosed in young girls and mainly affect Western cultures, they can occur in people of any gender, age, and background [ 11 ]. Recent years have been particularly challenging for people with eating disorders due to the COVID-19 pandemic, as restrictions on social life and difficult access to medical professionals may have negatively affected their mental health [ 16 , 17 ]. It was observed that in 2020, rates of eating disorder symptoms, depression, and anxiety were higher than in previous years [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, baseline general psychopathology scores were lower, that is, better, in patients exposed to the COVID‐19 pandemic. A recent systemic review, of 13 studies with a total of 7848 participants, on changes in eating‐disorder symptoms and associated psychological health issues during the COVID‐19 pandemic, indicated that the pandemic itself and the related social restrictions detrimentally impacted the mental health of the majority of individuals with eating disorders (Haghshomar et al, 2022 ). In our case, the difference in eating disorder psychopathology was not significant, but this could be due to the patient selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic and the consequent lockdowns have considerably influenced people’s mental health, particularly those with pre-existing conditions (e.g., eating disorders) [ 30 ]. However, some data suggest that the severity of food insecurity is linked to mental health status, particularly in low-income countries [ 31 ].…”
Section: Discussionmentioning
confidence: 99%